(untitled) (Iraqi Journal of Medical Sciences, 2024)
Early phases of coronavirus disease-2019 (COVID-19) are characterized by hypoxemic arteries that do not result in gasping, clinical deterioration may occur rapidly if hypoxemia is exacerbated by intra-pulmonary forcing, pulmonary vaso-compression fitness is not managed, and intravascular microthrombi are present with impaired lung diffusion. The goal of this hypothesis is to propose that COVID-19 may interfere with the glycolytic pathway by changing the amounts of intracellular metabolites, especially 2,3-bisphosphoglycerate (2,3-BPG), to aid in the release of oxygen from hemoglobin into the tissues, therefore preventing or treating hypoxia. As a conclusion, focusing on hypoxia as the primary cause of severe morbidity in COVID-19 patients is thought to result from an increased stability of the relax (R-form) of hemoglobin at the tissue level due to a decrease in glucose metabolite produced from glycolysis process in RBCs (decrease 2,3-BPG concentration in the blood). This theory proposes raising 2,3-BPG levels, which is to free up more O2 from the R-form of Hb in the tissues. Keywords: COVID-19, glucose metabolism, hemoglobin- oxygen binding, 2,3-bisphosphoglycerate Citation: AbdulKareem NGh, Mohammad FA. Interference of Coronavirus with glucose metabolism and its effect on affinity of hemoglobin binding to oxygen: A review. Iraqi JMS. 2024; 22(1): 1-12. doi: 10.22578/IJMS.22.1.1